STRENGTHENING STUDENT’S ENGLISH SKILLS THROUGH THE EXPOSURE OF AUDIO VISUAL-BASED ENGLISH STORIES - Muhammad Furqon; Raden Dinda Rahmalia Putri (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2018)
Nowadays, our life affected by fast-changing technology, so do the learning process. Many studies stated that Technology helps the students and teachers to achieve learning goals. One of the common techniques that usually help students to improve their English skills is by listening to audio visual- based English stories. In this study, a student is exposed to audio visual- based English stories in learning English, the goal of this study is to examine which skills that greatly impacted by the exposure of audio-visual English stories into student's learning. This study uses the Qualitative method, in which written test results, observation results, and recordings are used to obtain the data. By the end of the study, it can be concluded that Listening skill is the most affected skill from the exposure of the Audio-Visual based English Stories.